Ellipsoidal high-coercivity iron oxide nanoparticles and preparation method thereof

Synthesized ellipsoid high-coercive iron oxide nanoparticles by hydrothermal reaction method, solving the problem of harsh synthesis conditions of α-Fe2O3 and ε-Fe2O3 in the prior art, achieving the stability and magnetic performance of nanoparticles, and suitable for Various industrial applications.

CN119219067APending Publication Date: 2024-12-31NANJING UNIV OF POSTS & TELECOMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411641564.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

It is difficult to synthesize two types of iron oxide nanoparticles with stable and high coercive force and excellent magnetic properties at the same time, and the synthesis conditions are harsh, making it difficult to achieve rapid promotion in industrial applications.

Method used

By using the hydrothermal reaction method, ferrous chloride tetrahydrate was heated to 120-130°C in a mixed solvent of dimethylformamide, anhydrous ethanol and deionized water, and then cooled, and elliptical was obtained by centrifugation washing and drying. Spherical high coercive iron oxide nanoparticles are controlled to control the synthesis conditions to achieve the close binding of α-Fe2O3 and ε-Fe2O3.

Benefits of technology

The preparation of ellipsoid high-coercive iron oxide nanoparticles has high coercive force, excellent magnetic properties, and good stability. It is suitable for magnetic materials, catalysts and environmental protection fields. It is low in cost and simple in operation, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219067A_ABST
    Figure CN119219067A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: adding ferrous chloride tetrahydrate into a mixed solvent consisting of dimethylformamide, absolute ethyl alcohol and deionized water, stirring and dissolving, transferring the solution into a high-pressure reaction kettle lined with polytetrafluoroethylene, and reacting for 2-4 hours at the temperature of 50-60 DEG C to obtain the ellipsoidal high-coercivity iron oxide nano-particles. The preparation method comprises the following steps: adding ferrous chloride tetrahydrate into a mixed solvent consisting of dimethylformamide, absolute ethyl alcohol and deionized water; and heating to 120-130 DEG C at the rate of 1.5-10 DEG C / min for hydrothermal reaction, cooling to room temperature after the reaction is finished, centrifugally washing the reaction product, washing the solid product, drying, and finally grinding to obtain the product. Compared with the prior art, the method is simple to operate, easy to control and low in cost, alpha-Fe2O3 and epsilon-Fe2O3 in the prepared iron oxide nanoparticles are tightly combined, the iron oxide nanoparticles have high coercive force, excellent magnetic performance and good stability, and the iron oxide nanoparticles can be used as a magnetic material for separating magnetic substances and have good application prospects. And the catalyst can also be used for automobile exhaust purification, VOCs treatment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new material preparation, and in particular relates to ellipsoidal high-coercivity iron oxide nanoparticles and a preparation method thereof. Background Art

[0002] The metastable oxide ε-Fe2O3 is a rare polymorph of Fe2O3. Among the various Fe2O3 polymorphs, ε-Fe2O3 is the rarest phase with low natural abundance and an orthorhombic noncentrosymmetric structure. In recent years, it has attracted interest as a photoelectrochemical material and the only magnetoelectric Fe2O3 phase. This oxide was first discovered by Forestier and Gio-Ghillan in 1934, but in fact, this oxide has been a component of the Chinese pottery Tianwu glaze for about a thousand years. ε-Fe2O3 is an orthorhombic phase with space group Pna21. This phase has been the focus of intensive research due to its huge room temperature coercivity (HC) and the spin structure is ferromagnetic with a magnetization of about 0.1 T and a Curie temperature of 510 K. However, it is not completely clear whether the spin structure is collinear or non-collinear. It is reported that the coercivity Hc of ε-Fe2O3 nanoparticles is as high as 20kOe[2T], and they have a high saturation magnetization, making them an ideal choice for preparing high-performance magnetic materials. They can be used in data storage media, magnetic recording materials, etc. Due to their special surface properties, ε-Fe2O3 can also be used as a catalyst or catalyst carrier in catalytic reactions, especially in environmental protection technologies such as waste gas treatment and water treatment. Due to their good biocompatibility and adjustable size and morphology, ε-Fe2O3 nanoparticles also show potential value in bioimaging, drug delivery systems, and cancer treatment. However, ε-Fe2O3 has poor phase stability and only exists in the form of nanostructures. Due to its narrow temperature window stability, it is difficult to obtain as a single-phase material, and the synthesis conditions are relatively harsh.

[0003] α-Fe2O3 is the most thermodynamically stable structure of iron oxide under ambient conditions, and exhibits weak ferromagnetic properties due to the Dzyaloshinsky-Moriya mechanism (TC = 950K). It has n-type semiconductor properties, an indirect band gap of 2.2eV, and is low-cost, thermodynamically stable, environmentally friendly, abundant, non-toxic, and visible light absorptive. It is a potential visible light-driven photocatalyst. In addition, it is expected to become a low-dissipation spin-based computing device that can display ultrafast switching and has strong immunity to stray fields, and has a wide range of applications in catalysis, photonics, water treatment, sensors, electrochemistry, water decomposition, and magnetism.

[0004] Based on this, it is of great research significance to develop a method for preparing ellipsoidal high-coercivity iron oxide nanoparticles containing both α-Fe2O3 and ε-Fe2O3 products. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and provide a method for preparing ellipsoidal high coercive force iron oxide nanoparticles. The method is simple to operate. The prepared iron oxide nanoparticles contain both α-Fe2O3 and ε-Fe2O3 products, have high coercive force and excellent magnetic properties, and have good stability.

[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0007] A method for preparing ellipsoidal high coercivity iron oxide nanoparticles comprises the following steps:

[0008] (1) adding ferrous chloride tetrahydrate to a mixed solvent consisting of dimethylformamide, anhydrous ethanol and deionized water, stirring and dissolving the solution, transferring the solution to a polytetrafluoroethylene-lined autoclave, heating the temperature to 120-130° C. at a rate of 1.5-10° C. / min for a hydrothermal reaction, and cooling the reaction mixture to room temperature to obtain a reaction product;

[0009] (2) The reaction product is centrifuged and washed to obtain a solid product, the solid product is washed and dried, and finally ground to obtain ellipsoidal high coercivity iron oxide nanoparticles.

[0010] In step (1), the volume ratio of dimethylformamide, anhydrous ethanol and deionized water in the mixed solvent is 1:(15-30):5, more preferably 1:25:5.

[0011] Furthermore, in step (1), the heating rate is 4°C / min and the hydrothermal reaction time is 3-5h.

[0012] Furthermore, in step (2), the number of centrifugal washing is 3-4 times, and the rotation speed of centrifugal washing is 10000r / min.

[0013] Furthermore, in step (2), the drying temperature is 60°C.

[0014] The ellipsoidal high coercive force iron oxide nanoparticles are prepared by the method.

[0015] Beneficial effects of the present invention:

[0016] 1) The present invention provides a method for preparing ellipsoidal high coercive force iron oxide nanoparticles. The method is simple to operate, easy to control, and low in cost. The two materials α-Fe2O3 and ε-Fe2O3 in the prepared iron oxide nanoparticles are tightly combined, and rapid industrial application can be achieved.

[0017] 2) The present invention realizes the hydrothermal synthesis of α-Fe2O3 and ε-Fe2O3 hybrid superparticles for the first time, and the obtained iron oxide nanoparticles are ellipsoidal, have high coercivity and excellent magnetic properties, and have good stability.

[0018] 3) The iron oxide nanoparticles prepared by the present invention can be used as magnetic materials to efficiently separate magnetic substances from liquid or solid mixtures in the chemical and pharmaceutical industries; they can also be used as efficient catalysts or catalyst carriers in environmental protection fields such as automobile exhaust purification and VOCs (volatile organic compounds) treatment; they can also be used in the field of energy storage as part of the positive electrode material of lithium-ion batteries to improve the energy density and cycle life of the batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The XRD pattern of the iron oxide nanoparticles prepared in Example 1;

[0020] Figure 2 is the XRD pattern after refinement;

[0021] Figure 3 TEM, HRTEM and SAED images of the iron oxide nanoparticles prepared in Example 1;

[0022] Figure 4 Magnetic hysteresis loops of the iron oxide nanoparticles prepared in Example 1 at three different temperatures;

[0023] Figure 5 XRD pattern of the iron oxide nanoparticles prepared in Examples 1-6;

[0024] Figure 6 TEM image of the iron oxide nanoparticles prepared in Comparative Example 1;

[0025] Figure 7 This is the TEM image of the iron oxide nanoparticles prepared in Comparative Example 2. DETAILED DESCRIPTION

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the technical solutions of the present invention are clearly and detailedly described below in conjunction with the accompanying drawings and specific embodiments.

[0027] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0028] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0029] Example 1

[0030] A method for preparing ellipsoidal high coercivity iron oxide nanoparticles comprises the following steps:

[0031] (1) adding 10 mmol of ferrous chloride tetrahydrate to 50 mL of a mixed solvent consisting of dimethylformamide, anhydrous ethanol and deionized water in a volume ratio of 1:25:5, stirring and dissolving, transferring the solution to a polytetrafluoroethylene-lined autoclave, heating the temperature to 125° C. at a heating rate of 4° C. / min, hydrothermally reacting for 4 h, and then cooling to room temperature to obtain a reaction product;

[0032] (2) The reaction product was centrifuged and washed three times at a speed of 10000 r / min to obtain a solid product. The solid product was washed with deionized water and anhydrous ethanol, dried at 60° C. overnight, and finally ground to obtain iron oxide nanoparticles.

[0033] Figure 1 The XRD spectrum of the iron oxide nanoparticles prepared in Example 1 shows that the product is well crystallized. In addition, according to XRD analysis, the crystals are ε-Fe2O3 phase and α-Fe2O3 phase, and no other impurity peaks are detected, indicating that the product has high purity. The grain size of α-Fe2O3 is Dα-Fe2O3=28nm, and the grain size of ε-Fe2O3 is Dε-Fe2O3=25nm. Their lattice constants are respectively

[0034]

[0035] right Figure 1 After refinement, the refined map is shown in Figure 2 ,The refinement results show that the ratio of ε-Fe2O3 phase to α-Fe2O3 phase is 1:3.

[0036] The morphology and microstructure of all sample powders were analyzed using a Hitachi S-4800 scanning electron microscope (SEM) with an operating voltage of 5 kV. Figure 3 TEM, HRTEM and SAED images of the iron oxide nanoparticles prepared in Example 1, wherein: Figure 3 (a) and Figure 3 (b) TEM images at different scales. Figure 3 (c) is the HRTEM image. Figure 3 (d) is the SAED image, Figure 3 (a) and Figure 3 (b) It can be seen that the prepared iron oxide nanoparticles are uniform monodisperse microparticles with a length of about 1105.91nm and a diameter of about 592.76nm, and a uniform monodisperse hybrid superparticle is self-assembled from dozens or even hundreds of irregular polydisperse nanoparticles of about tens of nanometers. In order to confirm the formation of hybrid superparticle crystals, the nanoparticles were characterized by HRTEM. The lattice fringe spacing in the red area is about 0.367nm, corresponding to the (110) crystal plane of α-Fe2O3, and the lattice fringe spacing in the blue area is about 0.272nm, corresponding to the (122) crystal plane of ε-Fe2O3. The selected area electron diffraction (SAED) pattern shows that both ε-Fe2O3 and α-Fe2O3 phases exist.

[0037] The magnetic properties of the iron oxide nanoparticles prepared in Example 1 were measured using a Jinzhengmao vibrating sample magnetometer (VSM). A hysteresis loop was obtained at room temperature with a maximum applied magnetic field of ±10.1 kOe. After the residual magnetization and saturation magnetization were obtained from the hysteresis loop, the coercive force was calculated according to the following formula:

[0038]

[0039] Figure 4 Magnetic hysteresis loops of the iron oxide nanoparticles prepared in Example 1 at three different temperatures, where Figure 4 (a) is the hysteresis loop at 4K, Figure 4 (b) is the hysteresis loop at 300K. Figure 4 (c) is the hysteresis loop at 380K. Figure 4 (b) It can be seen that the coercive force (Hc) is 4.69kOe, the residual magnetization (Mr) is 0.2065emu / g, the saturation magnetization (Ms) is 0.2125emu / g, and the curve shows weak ferromagnetic behavior at room temperature (300K). At the maximum magnetic field H = 15kOe, the magnetization still has a positive slope, so the relationship between the magnetization and the magnetic field for these hybrid superparticles has not reached saturation. When the test temperature drops to 4K, Figure 4(a) It can be seen that Hc increases to 6.08kOe, the residual magnetization (Mr) is 1.545emu / g, and the saturation magnetization (Ms) is 1.905emu / g. It is worth noting that Figure 4 In (c), when the test temperature is 380K, Hc drops sharply to 0.27kOe, the residual magnetization (Mr) is 0.0835emu / g, and the saturation magnetization (Ms) is 0.2231emu / g, but the loop still shows weak ferromagnetic properties.

[0040] Example 2

[0041] In step (1), the heating rate is 1.5°C / min, and the rest is the same as in Example 1.

[0042] Example 3

[0043] In step (1), the heating rate is 2°C / min, and the rest is the same as in Example 1.

[0044] Example 4

[0045] In step (1), the heating rate is 6°C / min, and the rest is the same as in Example 1.

[0046] Example 5

[0047] In step (1), the heating rate is 8°C / min, and the rest is the same as in Example 1.

[0048] Example 6

[0049] In step (1), the heating rate is 10°C / min, and the rest is the same as in Example 1.

[0050] Figure 5 From the XRD diagrams of the iron oxide nanoparticles prepared in Examples 1-6, it can be seen that the phase ratios of ε-Fe2O3 and α-Fe2O3 are different due to different heating rates. In comparison, the curve of Example 1 (when the heating rate is 4°C / min) is smoother, and the strong peaks are more consistent with ε-Fe2O3 and α-Fe2O3, indicating that the product is well crystallized, and no other impurity peaks are detected, indicating that the product has high purity.

[0051] Comparative Example 1

[0052] In step (1), the volume ratio of dimethylformamide, anhydrous ethanol and deionized water in the mixed solvent is 1:10:5. The rest is the same as in Example 1.

[0053] The TEM image of the iron oxide nanoparticles prepared in Comparative Example 1 is shown in Figure 6 It can be seen that the material prepared in Comparative Example 1 has a large number of non-ellipsoidal nanoparticles, which is not suitable for subsequent research.

[0054] Comparative Example 2

[0055] In step (1), the volume ratio of dimethylformamide, anhydrous ethanol and deionized water in the mixed solvent is 1:5:5. The rest is the same as in Example 1.

[0056] The TEM image of the iron oxide nanoparticles prepared in Comparative Example 2 is shown in Figure 7 It can be seen that the material prepared in Comparative Example 2 is severely agglomerated and has a small amount of non-ellipsoidal nanoparticles, which is not suitable for subsequent research.

[0057] Comparative Example 3

[0058] Preparation of iron oxide nanoparticles by ball milling: Pour 100 g of grinding balls into a ball mill, then add 0.7 g of ferric nitrate nonahydrate and 3 g of hydrophilic fumed nano-silica, add a small amount of ethanol, seal the ball mill and grind at room temperature for 8 h, take out the product, dry it for 24 hours, and anneal it at 1000°C for 4 hours to obtain the finished product.

[0059] The preparation method of Comparative Example 3 requires an ultra-high temperature environment, is time-consuming, and has high costs. In addition, due to the high content of ε-Fe2O3, the stability is poor.

[0060] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing ellipsoidal high coercivity iron oxide nanoparticles, characterized in that: The steps include: (1) adding ferrous chloride tetrahydrate to a mixed solvent consisting of dimethylformamide, anhydrous ethanol and deionized water, stirring and dissolving the solution, transferring the solution to a polytetrafluoroethylene-lined autoclave, heating the temperature to 120-130° C. at a rate of 1.5-10° C. / min for a hydrothermal reaction, and cooling the reaction mixture to room temperature to obtain a reaction product; (2) washing the reaction product by centrifugation to obtain a solid product, washing the solid product and drying it, and finally grinding it to obtain ellipsoidal high coercivity iron oxide nanoparticles; In step (1), the volume ratio of dimethylformamide, anhydrous ethanol and deionized water in the mixed solvent is 1:(15-30):

5.

2. The method for preparing ellipsoidal high coercivity iron oxide nanoparticles according to claim 1, characterized in that: In step (1), the volume ratio of dimethylformamide, anhydrous ethanol and deionized water in the mixed solvent is 1:25:

5.

3. The method for preparing ellipsoidal high coercivity iron oxide nanoparticles according to claim 1, characterized in that: In step (1), the heating rate is 4°C / min and the hydrothermal reaction time is 3-5h.

4. The method for preparing ellipsoidal high coercivity iron oxide nanoparticles according to claim 1, characterized in that: In step (2), the number of centrifugal washing is 3-4 times, and the rotation speed of centrifugal washing is 10000r / min.

5. The method for preparing ellipsoidal high coercivity iron oxide nanoparticles according to claim 1, 2, 3 or 4, characterized in that: In step (2), the drying temperature is 60°C.

6. Ellipsoidal high coercivity iron oxide nanoparticles prepared by the method according to any one of claims 1 to 5.